The institute of the ombudsman (commissioner for human rights) in the public power system - Ashirbekova А.Б.; Abikenov А.А.; Saktaganova И.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The ombudsman institution plays an important role in the system of state bodies that ensure the rights and freedoms of people and citizens. In the article, in the context of the theory of separation of state power, the issue of the legal features of the ombudsman (human rights commissioner) in the system of state bodies raised. In addition, the concept and meaning of the ombudsman institution is revealed, and its place in the system of state authorities is analyzed. Three models of the ombudsman institute working in the states in modern times describes executive, independent and parliamentary. The purpose of the article is to determine its position in the system of state power by studying the legal status of the ombudsman institution, based on the norms established in national legislation. The works of foreign and domestic scientists who made a significant contribution to the study of the history of the formation and development of the Ombudsman Institute noted. Research methods of the Human Rights Ombudsman Institute described. In addition, the legal status of the ombudsman (Human Rights Commissioner) is described based on the articles of the Constitutional Law "On Human Rights Commissioner in the Republic of Kazakhstan" adopted on November 5, 2022.